Modification of selectivity and carbon deposition during the initial stages of the n-butane dehydrogenation over mono and bimetallic catalysts - Bocanegra, Sonia Alejandra (2013)
The initial carbon deposition and the generation of dehydrogenating selectivity during the initial steps of the reaction are investigated for Pt and PtSn catalysts supported on pure and Na-doped alumina by using a pulse technique (injection of n-butane pulses). Results demonstrate that Pt supported on pure alumina is not a proper dehydrogenation catalyst. It shows a high hydrogenolytic and cracking behavior and an important carbon formation that deactivates the catalyst. However the combined presence of tin and sodium inhibits not only the carbon deposition reactions but also the C-C breaking reactions, increasing in an important way the dehydrogenating selectivity to the different butenes to a value about 80%.